Combining Ability Estimates for Yield and Fiber Quality Parameters in Gossypium Hirsutum L. Hybrids - Mah-e-Jabeen Memon,; Moula Bux Kumbhar,; Muhammad Jurial Rind,; Mohammad Ibrahim Keerio ,; Shabana Memon, (Journal of Basic & Applied Sciences, 2016)
General and specific combining ability effects were discriminated in different parents and offspring to isolate the potential of genotypes used in diallel system to attain the genetic inheritance pattern ascertain with the nature of gene action. A six-by-six, hirsutum diallel excluding reciprocals, was analyzed for general and specific combining ability estimates and components of genetic variation to investigate the genetic retrospect and inheritance pattern of eleven quantitative and fiber quality characters. Hirsutum cultivars included CIM-506, BH-160, NIAB-111, CIM-497, NIAB-999 and RH-510. Some of the traits like boll number, boll weight and sympodia plant-1 did not reveal the highest GCA scoring parent for seed cotton yield. The ranking order for GCAs of the parents was not maintained from F1 to F2diallel set and the ranking order of the hybrids with respect to their SCA values was also not maintainable from F1 to F2 diallel set. Thus the hybrids could not maintain their superiority (or inferiority) of their SCA values.